Inclusion of patients with chronic kidney disease in randomized phase 3 clinical trials in patients with prostate, breast, lung, and colorectal cancer. (26th September 2022) - Delaye, Matthieu; Rousseau, Adrien; Try, Mélanie; Massard, Christophe; Campedel, Luca; Hilmi, Marc; Bagnis, Corinne
Abstract: The objective of this study was to determine the proportion of phase 3 clinical trials investigating a systemic therapy for patients with prostate, breast, lung, or colorectal cancer that excluded patients with Chronic Kidney Disease (CKD) and the exclusion criteria chosen, if any. A search was conducted using the ClinicalTrials.gov database to identify eligible studies. Of the 268 included trials, 185 (69%) had at least one renal exclusion criteria. Of these 185 trials, 116 (63%) had an undefined exclusion criterion. Only disease site was associated with exclusion of patients with CKD in the univariate analysis, but no factors in the multivariate analysis. There are several potential barriers to including patients with CKD in clinical trials. Nevertheless, solutions can be proposed to allow the inclusion of these patients. This would allow them to access to innovative therapeutic strategies, but also allow a better applicability of trial results to this patient population. Abstract : The majority of clinical trials restrict enrollment of patients with chronic kidney disease (CKD) and the exclusion criterion is undefined in most trials. Patients with CKD have therefore little access to innovation in oncology but solutions can be proposed to allow their inclusion in clinical trials.